Endocan: a novel predictor of endothelial dysfunction in obstructive sleep apnea syndrome. (24th May 2016) - Kanbay, Asiye; Ceylan, Erkan; Köseoğlu, Handan İnönü; Çalışkan, Mustafa; Takir, Mumtaz; Tulu, Selcan; Telci Çaklılı, Ozge; Köstek, Osman; Erek, Aybala; Afsar, Baris
Abstract: Background and Aims: Obstructive sleep apnea syndrome (OSA) is an independent risk factor for endothelial dysfunction and cardiometabolic diseases. Plasma endocan levels are elevated in a large number of diseases, and is a novel surrogate endothelial cell dysfunction marker. We aimed to assess the role of serum endocan level as a potential mechanism of endothelial dysfunction in OSA patients. Materials and Methods: This was a cohort study in which patients who had undergone a sleep study for diagnosis of OSA were recruited. Included patients were grouped according to apnea‐hypopnea index (AHI) as mild, moderate and severe OSA. Patients with AHI < 5 served as control group. Endothelial function was evaluated with flow‐mediated dilatation (FMD). Plasma endocan level was measured for all patients. Results: One hundred twenty eight OSA patients included (15 controls, 22 with mild, 22 with moderate and 69 with severe OSA). The mean age was 51.6 ± 11.9 years and 43.8% (56/128) of the study population was female. As expected, the prevalence of hypertension, diabetes and cardiovascular disease increased as the severity of OSA increased. Endocan levels were significantly higher and FMD measurements were lower in patients with OSA compared to healthy controls. There was a positive correlation between AHI and serum endocan levels (rho = 0.826, P  < 0.0001) and there was a negative correlation between AHI and FMD (rho = −0.686, P  < 0.0001) In addition, we observed a strong negative correlation between serum endocan level and FMD (rho = −0.613, P  < 0.0001). In linear regression analysis AHI was independently related both with endocan ( P  < 0.0001) and FMD ( P  = 0.011). Conclusion: Serum endocan level is strongly associated with the severity of OSA and endothelial dysfunction. Endocan might be a useful early novel marker for premature vascular endothelial system damage in OSA patients.